2021
DOI: 10.1021/acscatal.1c00110
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Engineering of Ir-Doped Ni-(Oxy)hydroxide Nanosheets for Enhanced Oxygen Evolution Activity

Abstract: Discovering highly active and stable electrocatalysts for the oxygen evolution reaction (OER) is critical to the commercial development of many next-generation energy conversion and storage devices, with Fe-doped nickel (oxy)­hydroxide representing one of the most promising OER catalysts developed to date. However, the active sites and mechanism of OER on Fe-doped nickel (oxy)­hydroxide catalysts remain unclear. To gain deeper insights into the role of metal dopants in enhancing OER activity, we explored here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 64 publications
3
51
0
Order By: Relevance
“…Noble metal-based materials are the state-of-the-art electrocatalysts for some important electrocatalytic reactions, such as Pt for the oxygen reduction reaction (ORR) and the HER and RuO 2 and IrO 2 for the OER. 34–40 However, for the UOR, noble metal-based electrocatalysts only show inferior performance, let alone their high costs and scarcity. 41 Fortunately, G. Botte and co-workers demonstrated that nickel exhibited much better UOR performance than some noble metals (Pt, Pt–Ir, and Rh) in an alkaline environment in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Noble metal-based materials are the state-of-the-art electrocatalysts for some important electrocatalytic reactions, such as Pt for the oxygen reduction reaction (ORR) and the HER and RuO 2 and IrO 2 for the OER. 34–40 However, for the UOR, noble metal-based electrocatalysts only show inferior performance, let alone their high costs and scarcity. 41 Fortunately, G. Botte and co-workers demonstrated that nickel exhibited much better UOR performance than some noble metals (Pt, Pt–Ir, and Rh) in an alkaline environment in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Thee lectron transfer number (n)o fS MO x -SMO (3.88) was comparable to Pt/C (3.92), which suggested anear-ideal ORR process involving afour-electron reduction pathway.Further,the epitaxially grown SMO x -SMO with Mn-O-Mn interfacial bonding offered better ORR stability than the unbonded heterojunctions (Figure S10). [25] In Figure 3f, SMO x -SMO/CNTs maintained 90 %o ft he initial current after 25 ha ta noperating voltage of 0.2 V( cf.P t/C,7 0% of initial current after 25 h). Furthermore,t he morphology and chemical composition of the material did not change significantly after the stability test (Figure S11).…”
Section: Methodsmentioning
confidence: 97%
“…To gain deeper insights into the role of metal dopants in enhancing (oxy)hydroxides’ OER activity, Ir-doped Ni(OH) 2 nanosheets were fabricated through a combination of hydrothermal assembly and liquid exfoliation, with the nanosheets transforming to Ir-doped NiOOH during OER and offering superior activity relative to pristine Ni(OH) 2 nanosheets or a commercial IrO 2 catalyst [ 196 ]. The DFT calculations with Hubbard U correction indicated that Ir doping increased the conductivity of β-NiOOH(001) and activated the oxygen site containing 3 Ni atoms (Ni 3 site).…”
Section: Electrocatalytic Performance Of Anion-mixed Electrocatalystsmentioning
confidence: 99%